RELATIONSHIP BETWEEN SOIL BULK DENSITY, ELECTRICAL CONDUCTIVITY AND POSSIBILITIES OF ECOLOGICAL DIAGNOSTICS - Gulaliyev, Chingiz (Journal of the Belarusian State University. Ecology, 2026)
The article explores the relationship between soil bulk density and electrical conductivity as a tool for ecological diagnostics of structural changes. Soil is a key ecosystem component whose functionality largely depends on its structure, density, and moisture content. Intensive use of heavy agricultural machinery leads to soil compaction, reduced porosity, and structural degradation, which in turn affects water infiltration, gas exchange, and biological activity. Experimental studies were carried out on three soil types of the Kura-Araz lowland: meadow-gray, gray-meadow, and alluvial-meadow soils. Electrical conductivity was measured in the frequency range of 0.4–10 MHz under different moisture levels (10–24 %) and densities (1.1–1.4 g/cm³). The results showed a strong linear relationship between electrical conductivity and soil bulk density, which became more pronounced with increasing moisture content. The highest electrical conductivity values were recorded in alluvial–meadow soils, while the greatest sensitivity to compaction was observed in gray-meadow soils. Correlation analysis revealed strong positive relationships (r = 0.95–0.99), and the regression models demonstrated a coefficient of determination R² > 0.90. These findings confirm that electrical conductivity can be considered an integral indicator of soil condition, reflecting the combined effects of physical and hydrothermal parameters. The application of electrical conductivity provides opportunities for early diagnosis of soil degradation, optimization of agricultural practices, and the development of ecological monitoring systems. Moreover, this methodology can be integrated into precision agriculture and applied in interregional comparisons, offering a reliable scientific basis for sustainable land-use strategies.
Keywords: soil grounding; electrical conductivity; environmental diagnostics; compaction; porosity; soil degradation; monitoring; agroecosystems